Axiological circumscribing of the ongoing training of history teachers in the context of current education - Daniela VACARCIUC (Acta et Commentationes, Sciences of Education, 2023)
The article addresses a current issue concerning the ongoing training of teachers history schoolchildren in the process of modernization of education through the prism of a new vision, such as that of batik axiology or deep values. The advantages of the problematological approach in continuous training of history teachers, which also proposes a change of perspective. Moreover, the DACI formative ensemble is analyzed, which includes some profound values (justice, authenticity, thrift, integrity) and some competency-forming actions are illustrated problematological of school teachers in the consensus of the new requirements of education.